2009
DOI: 10.1370/afm.939
|View full text |Cite
|
Sign up to set email alerts
|

Screening Colonoscopies by Primary Care Physicians: A Meta-Analysis

Abstract: PURPOSE There is currently too few endoscopists to enact a national colorectal cancer screening program with colonoscopy. Primary care physicians could play an important role in fi lling this shortage by offering screening colonoscopy in their practice. The purpose of this study was to examine the safety and effectiveness of colonoscopies performed by primary care physicians. METHODSWe identifi ed relevant articles through searches of MEDLINE and EMBASE bibliographic databases to December 2007 and through manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 30 publications
5
41
1
5
Order By: Relevance
“…There was no significant difference among the three pathological rate of colon cancer screening in the setting of hospital based in Thailand was 30.9% and 16.5% respectively. This data was compatible with the results from previous studies in many countries (Liou et al, 2007;Parente et al, 2009;Wilkins et al, 2009;Strnad and Sonogoric, 2010;Taber et al, 2010;Diamon et al, 2011;Leung, 2011;Long et al, 2011) which reported 25-48% of adenoma detection rate and recommended colon cancer screening in average-risk people over 50 years old. However, it is different from Taiwanese study (Tracy et al, 1976) which stated only 13% of polyp detection rate.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There was no significant difference among the three pathological rate of colon cancer screening in the setting of hospital based in Thailand was 30.9% and 16.5% respectively. This data was compatible with the results from previous studies in many countries (Liou et al, 2007;Parente et al, 2009;Wilkins et al, 2009;Strnad and Sonogoric, 2010;Taber et al, 2010;Diamon et al, 2011;Leung, 2011;Long et al, 2011) which reported 25-48% of adenoma detection rate and recommended colon cancer screening in average-risk people over 50 years old. However, it is different from Taiwanese study (Tracy et al, 1976) which stated only 13% of polyp detection rate.…”
Section: Discussionsupporting
confidence: 92%
“…Colorectal cancer (CRC) is a leading cause of cancer death worldwide (Wilkins et al, 2009). It is the second most common cancer in most Western countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the recent implementation of several nationwide screening programs using FIT in Western countries, it is important to address potential factors which may affect performance of these tests, as this knowledge may help to design tailored screening strategies. In our study conducted in subjects with average risk, the adenoma detection rate, one of the quality indicators for colonoscopy, was 26% and is in line with previously published data ranging from 21% to 29% (23)(24)(25). It should be acknowledged that colonoscopy has a miss rate of up to 22% for polyps of any size, as has been reported by a recent meta-analysis of back-to-back colonoscopy studies (26).…”
Section: Discussionsupporting
confidence: 91%
“…O sangramento após colonoscopia tem relação direta com procedimento diagnóstico como biópsia e terapêutico como polipectomia 1,2,5,6,8,9,11,12 , assim como evidenciado no atual estudo. Este sangramento pode ocorrer durante o procedimento (quatro casos no presente estudo) ou mesmo depois de dias 2,7,8,9,11 (um caso) e tem maior incidência quanto maior o pólipo ressecado ou sua característica séssil 1,6 . A perfuração apesar de menos prevalente, apresenta elevado risco ao paciente, podendo ser letal.…”
Section: Tabela 6 -unclassified